Changes in Richness and Species Composition after Five Years of Grazing Exclusion in an Endemic Pasture of Northern Mexico - José Ramón Arévalo; Cristina González-Montelongo; Juan A. Encina-Domínguez; Eduardo García; Miguel Mellado (Land, 2022)
A well-managed grazing system improves the productivity and health, and it is important to promote sustainability. We analyzed the impact of grazing on the Sierra de Zapalinamé protected area in north Mexico. Our hypothesis was that grazing modifies species composition, richness, and nutrients after grazing exclusion for five years. In this area, eight plots were excluded from grazing, and species richness, evenness, and plant functional types for five years were monitored. This monitoring was also carried out on eight control plots adjacent to the excluded plots. Soil samples were collected from each plot in the fifth year of exclusion for nutrient content analysis. Grazing discriminated plant species composition after five years between excluded and control plots, but not species richness and evenness. In addition, exclusion increased grass cover and decreased forb cover. Indicator species for excluded and control sites were identified. It was concluded that part of the pastures can be excluded from grazing as a way to analyze changes in this protected area and promote greater plant diversity.